A bela rosa e seus espinhos: semeando a preservação do bairro Hamburgo Velho (1970-1980) - Souza, Quésia Katúscia Gasparetto de (Universidade do Vale do Rio dos Sinos, 2018)
The purpose of this dissertation is to preserve the historical and cultural heritage of the Hamburg Velho district, located in the city of Novo Hamburgo, State of Rio Grande do Sul. It analyzes the existing links between memory, public policies, patrimony and the identity of colonization German in the historic quarter of Hamburgo Velho making use of oral history. It investigates the actions of the community in preserving the neighborhood from the commemorations of the Sesquicentenary of the German Immigration in the state in 1974. The plastic artist Ernesto Frederico Scheffel participates of this exhibition and from this festivity, together with members of the community articulate in favor of the preservation of the architectural set and the history of Hamburgo Velho throughout the decades of 1970 and 1980, temporal cut investigated in this work. Sectional and councils are formed to discuss patrimonial issues and actions because the municipal public power lacked public policies, laws and oversight bodies. The Historical and Artistic Heritage Reclamation of Old Hamburg is created in 1980 and as these mobilize alliances are formed. Opinions and reactions generate conflicts between residents of the neighborhood versus the preservationist movement. Historical houses are preserved and used since then as museums: Ernesto Frederico Scheffel Foundation (Art Museum) and Casa Schmitt Presser Museum (Museum of History).
Keywords: Patrimônio; Memória; Identidade; Hamburgo Velho; Novo Hamburgo; Patrimony; Memory; Identity; Hamburgo Velho; Novo Hamburgo; ACCNPQ::Ciências Humanas::História